Pengembangan Manajemen Santri dalam Pondok Pesantren (Studi Kasus pada Pondok Pesantren Nurul Qona’ah Desa Karangkedawung Kecamatan Mumbulsari Kabupaten Jember) - Aditia, Bambang Eko (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2019)
Management of an Islamic boarding school institution in an effort to empower santri needs to hold conceptual and strategicoperational efforts so as to be able to prepare qualified human resources who are ready to compete in the era of globalizationwhich is full of competence. The focus of this research is (1) How is planning in the development of santri (2) How is supervision inthe development of santri. In achieving the research objectives, the method used is a phenomenological qualitative approach, as for the type of research case study, the data in this study consisted of primary and secondary data while in selecting and determining informants in this study, using the technique of snowball sampling. For data collection using procedures, interviews, participant observation, and documentation. Furthermore, in analyzing the data used descriptive qualitative data analysis techniques, with steps: (a), data reduction, (b) data presentation, and (c) drawing conclusions. While testing the validity of data through, Presistent Observation, Triangulation sources, Peerderieting